A CLINICAL COMPARATIVE STUDY OF ULTRASOUND-GUIDED POPLITEAL NERVE BLOCK WITH 0.5% BUPIVACAINE HYDROCHLORIDE WITH AND WITHOUT 8MG DEXAMETHASONE FOR KNEE SURGERIES - KALAPALA, RAMESH; BANDRAPALLI, EMEEMA; NEERAJA, MALAPOLU; ANAND (International Journal of Current Pharmaceutical Research, 2023)
Objective: This study aimed to see how adding dexamethasone 8 mg to 0.5% bupivacaine affected the length of sensory and motor blockage of the popliteal sciatic nerve in ankle and foot surgeries. Methods: This prospective randomized clinical comparison trial enrolled 60 patients with American Society of Anesthesiologists (ASA) physical status grades III and IV, aged 50-80 y, scheduled for ankle and foot procedures from March 2023 to July 2023. Patients were assigned into two groups of 30 at random. 28 ml of 0.5% bupivacaine and 8 mg dexamethasone were given to Group D. Group N was given 28 ml of o.5% bupivacaine and 2 ml of NS. Here, 20 ml was used for sciatic nerve block and 10 ml for saphenous nerve block. Results: The mean onset of sensory block in group D was 23.2±6.8 min, while 21.7±6.9 min in group N (p 0.3999). This was not statistically significant. The onset of motor block was 22.9±7.9 in group D and 22.3±7.1 in group N, which were statistically insignificant (p 0.7581). The duration of the motor block in group D was 11.3±3.2 h, whereas it was 5.9±2.3 h in group N (p 0.0001), which was statistically significant. The length of the sensory block in group D was 14.9±3.8 h, while it was 8.3±3.4 h in group N (p 0.0001), which was also statistically significant. The VAS score in group N was significantly higher than in group D; it began 3 h after surgery and remained at 4 h, 5 h, 6 h, 8 h, 10 h, and 12 h. All 30 patients in Group N required their first rescue analgesia during the first 12 h postoperatively. In contrast, only 12 patients (40%) required their first analgesia within the first 12 h, and 18 (60%) requested their first analgesia within the second 12 h. Conclusion: Adding 8 mg dexamethasone to 0.5% Bupivacaine hydrochloride in ultrasound-guided popliteal and saphenous nerve blocks for ankle and foot procedures extends postoperative sensory and motor block duration.